Domestic and Global Challenges in Indonesia's Initiatives for Sustainable Development in the South Pacific - Lubis, Adelita; Baharuddin, Aswin; Lubis, Mia Aulina (Journal of International and Local Studies, 2026)
Following the launch of the Pacific Elevation policy in 2019, Indonesia intensified its sustainable development initiatives in the South Pacific through LDKPI grants, South-South and Triangular Cooperation, and the Indonesia-Pacific Forum for Development. This study applies Putnam's two-level game framework to analyze the domestic and global challenges affecting these initiatives and the interactions between the two levels. The study employed a qualitative, descriptive-analytical approach, employing a desk study of official documents and scientific literature from 2019–2025, with source triangulation as a validity mechanism. The results identified domestic challenges as limited fiscal scale, institutional fragmentation, and the double burden of the Papua issue. At the global level, challenges include intense donor competition, legitimacy challenges from Pacific nations' diplomatic agencies, and the misalignment of cooperation portfolios with regional climate priorities. The interaction of these two levels of challenges narrows Indonesia's policy win-set, resulting in observed strategies that include small grants to the human development sector, the Pacific family narrative, triangular partnerships, and island identity diplomacy. These strategies are best understood as rational adaptations to the limited available space for maneuver. This research's theoretical contribution is the identification of sovereignty defense as a driving force for South-South development cooperation, a theme not yet addressed in emerging donor literature.